Ultraviolet A absorption coefficients of contact lenses for use in contact lens assisted corneal crosslinking for thin Corneas - Kelechi C. Ogbuehi (Scientific Reports, 2025)
Abstract The purpose of this study was to compare the UVA absorption coefficients of multiple hydrogel and silicone hydrogel lenses (with and without pre-soaking in riboflavin) to those reported for the human cornea. The study also assessed the effect of different contact lens pre-soak times (in riboflavin) on the measured UVA absorption coefficients. Five lenses each of Omafilcon A, Nelfilcon A and Somofilcon A were pre-soaked in riboflavin and UVA absorption was assessed. Six lenses each of two hydrogel (Omafilcon A and Nelfilcon A) and three silicone hydrogel (Comfilcon A, Lotrafilcon A, and Samfilcon A) lenses were assessed before and after a 30-minute soak in riboflavin. One-way ANOVA was used for all comparisons. Absorption coefficients, without riboflavin, for Omafilcon A, Nelfilcon A and Somofilcon A were: 8.6 ± 1.2 cm−1; 11.7 ± 3.4 cm−1; 51.9 ± 2.9 cm−1, respectively. These absorption coefficients were all significantly greater (p < 0.0001) after pre-soaking in riboflavin. The average (+/- SD) coefficients of the different lenses in the main study, without riboflavin, were: 9.1 +/- 0.7 cm-1; 10.9 +/- 2.1 cm-1; 6.9 +/- 2.0 cm-1; 16.2 +/- 2.8 cm-1; and 17.8 +/- 3.2 cm-1, respectively, for: Omafilcon A; Nelfilcon A; Comfilcon A; Lotrafilcon A; and Samfilcon A. Absorption coefficients were all significantly greater (two-tailed, paired Student’s t-test, p < 0.0001) with riboflavin. Oxygen permeability is a better predictor of the absorption coefficient (and therefore of the contact lens-assisted corneal collagen crosslinking effectivity) of a soft contact lens than water-content.